2015
DOI: 10.1182/blood-2014-11-568881
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenesis beyond the cancer clone(s) in multiple myeloma

Abstract: Over the past 4 decades, basic research has provided crucial information regarding the cellular and molecular biology of cancer. In particular, the relevance of cancer microenvironment (including both cellular and noncellular elements) and the concept of clonal evolution and heterogeneity have emerged as important in cancer pathogenesis, immunologic escape, and resistance to therapy. Multiple myeloma (MM), a cancer of terminally differentiated plasma cells, is emblematic of the impact of cancer microenvironmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
231
0
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 242 publications
(236 citation statements)
references
References 127 publications
2
231
0
3
Order By: Relevance
“…Despite the fact that knowledge about the biology of MM PCs has greatly increased in recent years, 1 the same does not apply to AL. Thus, the cytogenetic profile of patients with AL has only been reported in a few studies [2][3][4][5][6][7] that investigated a limited number of alterations (eg, IGH translocations or 13q and 17p deletion).…”
Section: Introductionmentioning
confidence: 97%
“…Despite the fact that knowledge about the biology of MM PCs has greatly increased in recent years, 1 the same does not apply to AL. Thus, the cytogenetic profile of patients with AL has only been reported in a few studies [2][3][4][5][6][7] that investigated a limited number of alterations (eg, IGH translocations or 13q and 17p deletion).…”
Section: Introductionmentioning
confidence: 97%
“…1 Osteolytic lesions are a hallmark of this disease, and the loss of bone is largely caused by increased osteoclast activity.…”
Section: Introductionmentioning
confidence: 99%
“…4 It was also shown that normal or MM-derived exosomes differentially affect MM cell homing and growth in vivo. 15 Altogether, these studies warrant the need for a better understanding of the role of the malignant BM microenvironment in MM.…”
mentioning
confidence: 99%